(untitled) (Journal of Misan Researches, 2021)
Narrative dreams have not sufficiently been given their deserved share of the research, although literature, poetry, and prose, abounds it the presence of dreams in the etiquette of nations and their culture is evidence of their effectiveness in the social and spiritual life of peoples. Dreams reveal what is not told and disclose the future, and the suppressed and pent-up desires. That is why this research examines the functions of developing visions and narrative dreams in literature The research paper is divided into two parts: theoretical and applied frameworks. In the theoretical framework, the paper deals with narrative visions and dreams; in this part, the definition and the difference between them are clearly presented. The research also examines the functions of the three narrative dreams and visions which are Cultural functions: (the function of prophecy and foresight - the cognitive function - the cultural mediator); Technical functions: (overlapping worlds –chronological overlapping– writer/ narrator mask); linguistic function: - building pictures - showing the untold - the formal function; Psychological functions: (self-disclosure, compensation for losses, unconscious activation ) As for the applied framework, the study deals with a selected sample of dreams and literary texts. It was analyzed and disclosed the three functions that has been proved in the theoretical framework. Among these dreams: "The vision of the king of Egypt for the seven cows" which was analyzed according to the ritual religious-cultural symbols of ancient Egyptian society The research also examines narrative visions and dreams in literature in "The Epic of Gilgamesh", "The Biography of ibn Hisham" and "Tales of a Thousand and One Nights". Finally, the research also studies selected models of narrative texts, particularly in the Iraqi novel to reveal the functions of narrative dreams in them.